A pesca de curral na praia de Bitupitá, Ceará: dilemas de povos e comunidades tradicionais frente a políticas de desenvolvimento - Araújo, Antônia Gabriela Pereira de (2016)
The present dissertation is the result of an ethnographic research, carried out between July 2013 and June 2015, whose main purpose is to ethnographically record the processes of changes experienced by the fishermen of Praia de Bitupitá (Barroquinha- CE) of development policies, in particular tourism public policies, wind energy industry and shrimp industry. The research on the techniques, knowledge and logic that governs the way of life of the fishermen of that beach allowed to verify that the activity of the fishing of corral and the way of production and reproduction of these families of fishermen are put in play before the economic activities that settle in the region. The methodological basis was based on a procedural ethnographic approach of the experiences of changes lived in the locality from the articulation between anthropology and public policies. This dialogue between the two fields of study allowed for the understanding of both the processes of change experienced by the communities traditionally studied by the anthropologists (Rodrigues, Ortolan and Gonçalves, 2014), and allowed the identification and analysis of the different social agents involved in that situation, of power and interests between these agents and the interactions between them with the biophysical and social means. I take as a starting point the idea that the greater the number and diversification of development policies, the more local practices, such as clientelistic relations, are accentuated, but, on the other hand, local identities can be strengthened. The present ethnography makes it evident that the implementation of public development policies in regions inhabited by traditional peoples and communities occurs in a conflicting way due to the absence of regularization and territorial planning in these areas and the absence of efficient legal mechanisms that guarantee the rights of traditional peoples (PNPCT), as well as by the strong social asymmetries that translate into inequalities of power in the political arena and in the public authorities, making the balance for the holders of local power fall and if on the one hand they intensify the struggle between the rival groups, on the other they further subjugate those situated in the lower position in the field of forces.